Asylum According To The Rules Of International Law - جامع , شادي; صقور, جعفر (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Human by instinct is as asocial being who seeks to live in peace and safe and stays away from wars. But, because of the increased spread of armed conflicts caused the asylum problem and via leaving the place of origin and going to another safe country, and because of the dramatic increase in this phenomenon the international community become more interested in asylum and make international treaties to organize the legal status of refugees. In our search, we will present the most important legal points related to this topic.